Conventional and functional magnetic resonance imaging features of late subacute cortical laminar necrosis in a dog. (23rd May 2019) - Alisauskaite, Neringa; Wang‐Leandro, Adriano; Dennler, Matthias; Kantyka, Marta; Ringer, Simone K.; Steffen, Frank; Beckmann, Katrin
Abstract: Cerebral cortical laminar necrosis (CLN) is a consequence of severe hypoxic, ischemic, or hypoglycemic events. In humans, these cortical lesions show characteristic linear T1‐weighted (T1W) hyperintensity in the late subacute stage. Limited information reporting magnetic resonance imaging (MRI) findings in dogs affected by CLN is available. A 3‐year‐old Belgian Shepherd dog was referred 8 days after sudden onset of blindness after general anesthesia. Neurological examination showed central blindness and mild ataxia. Three‐Tesla MRI examination of the brain revealed bilateral asymmetrical areas of T2‐weighted hyperintensity within the occipital, parietal, temporal, and frontal cortex, involving gray and white matter. Furthermore, linear T1W‐hyperintense lesions were found in the cerebral cortex of the same areas and showed heterogeneous contrast enhancement. Perfusion‐weighted images revealed hyperperfusion in the affected regions. Lesions were compatible with subacute CLN with corresponding edema suspected to be secondary to anesthesia‐related brain hypoxia. Three‐Tesla MRI enabled identification of the laminar pattern of the cortical lesions.